Composite noble metal catalyst as well as preparation method and application thereof

By introducing inert oxides modified with surface functional groups with high specific surface area into the catalyst and forming reinforced bonds with ionomers to build gradient pores, the problem of difficult controllability of the catalytic layer structure in the prior art is solved, and a significant improvement in the performance of the catalytic layer is achieved.

CN119685875APending Publication Date: 2025-03-25TAN KAH KEE INNOVATION LAB +1

Patent Information

Application Number
CN202411803087.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently construct an orderly three-phase interface, and the operation process is cumbersome, making it difficult to achieve an orderly and controllable structure of the micro-nano structure of the catalytic layer, which restricts the continued improvement of the performance of the catalytic layer.

Method used

By introducing inert oxides modified with surface functional groups with high specific surface area into the catalyst, the stability of the slurry is promoted, and agglomerates are constructed through strengthening bonding with ionomers, and gradient pores are constructed from the molecular level.

Benefits of technology

The porosity and pore size distribution of the catalytic layer are significantly improved and the material transport process is improved. Especially at high current density, the material transport impedance is reduced by 99%, and the performance is improved by 156mV.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685875A_ABST
    Figure CN119685875A_ABST
Patent Text Reader

Abstract

The invention provides a composite noble metal catalyst as well as a preparation method and application thereof, and relates to the technical field of proton exchange membrane electrolyzed water. The composite noble metal catalyst comprises a noble metal oxide catalyst and a modified inert oxide, wherein the specific surface area of the modified inert oxide is greater than or equal to 50m < 2 > / g; a modifier adopted for modification comprises any one or a combination of at least two of a fluorine ion-containing inorganic substance, perfluoro-substituted organosilane or organic amine silane. According to the invention, the modified inert oxide with high specific surface area is introduced into the catalyst, so that the pores of the catalyst layer are accurately regulated and controlled from the molecular level, and the uniformity and repeatability of regulation and control are improved. A pore gradient is constructed in multiple dimensions, a microporous structure is formed inside the aggregate, mesopores and macropores are formed outside the aggregate, and the material transmission process is further promoted. The electrolytic performance of the PEM electrolyzed water is enhanced, and the stability of the PEM electrolyzed water is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for water electrolysis anodes, and in particular to a composite noble metal catalyst and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane water electrolysis (PEMWE) has become a key technology for green hydrogen production due to its high energy conversion efficiency, fast response speed, high-purity hydrogen production, and clean and pollution-free advantages. It is widely used in energy storage, transportation, industrial production and other fields. Membrane electrode (MEA) is one of the core components of PEM water electrolysis hydrogen production technology, usually composed of proton exchange membrane (PEM), catalyst layer (CL) and porous transport layer (PTL). Among them, the catalyst layer is the core site of electrochemical reactions for multiphase material transport and energy conversion, which is crucial for PEM water electrolysis hydrogen production.

[0003] The electrochemical performance and stability of the catalytic layer mainly depend on the constructed porous electrode structure, which requires balancing the proton, electron and water / gas transport processes at the same time, so as to construct more three-phase reaction interfaces. Among them, pores, as important water / gas transmission channels, are one of the important indicators for evaluating electrode performance. Especially under harsh working conditions of high current density, the gas production rate of water electrolysis is too fast, and the gas that is not discharged in time will cover the surface of the active sites, hindering the further occurrence of electrochemical reactions. At the same time, accompanied by additional material transport resistance, the performance is further reduced. More seriously, this may lead to local high current density and stress, aggravate the corrosion degradation and mechanical damage of the catalytic layer, and ultimately affect the operating performance and operational stability of the equipment. Therefore, it is crucial to design and prepare an integrated porous electrode, which helps to improve the performance expression of the catalyst under working conditions, thereby promoting the low-cost hydrogen production route of PEM water electrolysis.

[0004] At present, a variety of schemes for preparing porous catalytic layers have been developed, such as adjusting the pores of the catalytic layer by regulating the morphology of the catalyst itself, and various methods for preparing one-dimensional nanowires and two-dimensional nanosheet structures have been developed. Pore-forming agents such as inorganic additives / soluble organic matter are introduced in combination with the sacrificial template method to construct pores in the catalytic layer with different structures. On this basis, there are also patents that innovatively propose ice particles crystallized from water as templates, and further optimize the above schemes through steps such as preparing water-based slurry, casting, water-oriented crystal growth, and freeze-drying. Or through process adjustments, such as multiple coating / layered preparation methods, electrodes with graded pore gradients can be prepared.

[0005] CN118439666A discloses a method for promoting the transport of catalytic layer materials by regulating the morphology of catalysts, using carboxyl functional group small molecules to regulate the formation of catalysts with two-dimensional assembly characteristic structures, but this method is limited to iridium-based materials and lacks certain universality. At the same time, the catalyst structure will be destroyed when the catalyst layer slurry is prepared by ball milling, and it is difficult to directly affect the catalyst layer structure by simple catalyst structure regulation.

[0006] CN103531826A discloses a method for constructing a nanoporous membrane electrode for a direct methanol fuel cell based on a sacrificial template method, by adding oxide templates of different sizes and shapes to regulate the structure of the internal nanopores. The pores constructed by this method need to undergo a template removal process, which is relatively cumbersome, and the process of removing the template is difficult to maintain the structure of the catalytic layer. At the same time, due to incomplete removal of the template, new impurity ions may be introduced, bringing additional electrode poisoning problems. A similar method is also mentioned in CN118345408A, which further expands the oxide template to soluble organic matter and soluble salts, but the above-mentioned defects also exist.

[0007] CN110212224A discloses a method for making holes in the cathode electrode layer of a proton exchange membrane fuel cell using ice particles as a template, which reduces mass transfer resistance and improves battery performance by constructing an ordered porous electrode structure. Similar schemes are mentioned in CN113839052A, CN103319182A and CN118213541A, but these schemes involve low-temperature treatment of proton membranes and subsequent vacuum freeze drying, which are complicated to operate and may lead to non-repeatability of the structure, which is not conducive to large-scale preparation.

[0008] In summary, none of the above solutions can efficiently construct an ordered three-phase interface, and the operation process is relatively cumbersome, making it difficult to achieve the orderly and controllable construction of the micro-nanostructure of the catalyst layer, which restricts the continued improvement of the performance of the entire catalyst layer. At the same time, they may bring new device poisoning problems due to incomplete removal, which is not conducive to the stable operation of the membrane electrode. There is an urgent need for a universal solution that can accurately control the porous structure of the catalyst layer at a more microscopic molecular level.

[0009] In view of this, the present invention is proposed. Summary of the invention

[0010] The purpose of the present invention is to provide a composite noble metal catalyst and its preparation method and application. The composite noble metal catalyst of the present invention is to introduce an inert oxide modified with a surface functional group with a high specific surface area into the catalyst to promote the stability of the slurry and prevent the sedimentation of particles during the pore formation process; at the same time, by modifying the functional group on the surface of the inert oxide, it can react with the sulfonic acid side chain of the ionomer through a strong chemical bond to achieve a rapid adsorption effect, thereby constructing an aggregate, and finally regulating and constructing gradient pores at the molecular level, and promoting the performance expression of the working condition of PEM water electrolysis through a stable and efficient material transmission channel.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] In a first aspect, the present invention provides a composite noble metal catalyst, wherein the composite noble metal catalyst comprises a noble metal oxide catalyst and a modified inert oxide;

[0013] Wherein, the specific surface area of ​​the modified inert oxide is ≥50m 2 / g; and the modification used in the modification includes any one or a combination of at least two of fluorine-containing inorganic substances, perfluorinated substituted organic silanes or organic amine silanes.

[0014] Preferably, the fluoride ion-containing inorganic substance comprises a fluoride salt.

[0015] Preferably, the fluoride salt is selected from any one of sodium fluoride, potassium fluoride, lithium fluoride or ammonium fluoride, or a combination of at least two thereof, preferably sodium fluoride.

[0016] Preferably, the perfluorinated organosilane is selected from any one of trimethoxyfluorosilane, heptadecafluorodecyltrimethoxysilane or 1H, 1H, 2H, 2H perfluorodecyltriethoxysilane or a combination of at least two thereof.

[0017] Preferably, the organic amine silane is selected from any one of aminopropyltriethoxysilane, aminopropyltrimethoxysilane or anilinomethyltriethoxysilane, or a combination of at least two thereof.

[0018] Preferably, the inert oxide is selected from any one or a combination of at least two of titanium oxide, tin oxide, zirconium oxide, niobium oxide, tantalum oxide, tungsten oxide or silicon oxide.

[0019] Preferably, the mass ratio of the inert oxide to the modifier is 1:(0.03-5.81).

[0020] Preferably, the noble metal oxide catalyst is selected from any one of ruthenium oxide, rhodium oxide, iridium oxide or platinum oxide, or a combination of at least two thereof, and possible supported noble metal catalysts.

[0021] Preferably, the mass ratio of the noble metal oxide catalyst to the modified inert oxide is (1-20):1.

[0022] In a second aspect, the present invention provides a method for preparing the composite noble metal catalyst as described in the first aspect, wherein the method for preparing the composite noble metal catalyst comprises the following steps:

[0023] The noble metal oxide catalyst and the modified inert oxide are mixed to obtain the composite noble metal catalyst.

[0024] Preferably, the mixing method includes any one of stirring, ultrasound, ball milling, solution wet mixing and drying, or a combination of at least two thereof, preferably ball milling.

[0025] Preferably, the rotation speed of the ball mill is 200 to 600 rpm, and the time of the ball mill is 0.5 to 3 hours.

[0026] Preferably, when the modified substance used in the modification is a fluorine-containing inorganic substance, the modified inert oxide is prepared by the following steps:

[0027] (a) ultrasonically dispersing an inert oxide into a solution of a fluoride ion inorganic substance, adjusting the pH of the system to 2.5 to 3.5, and stirring to obtain a fluoride ion solution of the inert oxide;

[0028] (b) centrifuging the fluoride ion solution of the inert oxide, collecting the solid precipitate, and then redispersing the solid precipitate, washing it, and drying it to obtain the fluoride ion modified inert oxide.

[0029] Preferably, in step (a), the mass volume ratio of the solution of the inert oxide and the fluorine ion-containing inorganic substance is 1 g: (100-150) mL.

[0030] Preferably, in step (a), the concentration of the solution containing the inorganic fluoride ion is 0.1-10M.

[0031] Preferably, in step (a), the solvent in the solution of the fluorine ion inorganic substance is selected from any one of water, ethanol or methanol or a combination of at least two thereof, preferably water.

[0032] Preferably, in step (a), the reagent used to adjust the pH of the system is an inorganic acid, preferably any one or a combination of at least two of nitric acid, sulfuric acid, hydrochloric acid or phosphoric acid, more preferably nitric acid.

[0033] Preferably, in step (a), the concentration of the inorganic acid is 0.1-1M.

[0034] Preferably, in step (a), the stirring speed is 400 to 800 rpm, and the stirring time is 1 to 3 hours.

[0035] Preferably, in step (b), the centrifugal rotation speed is 4000-6000 rpm.

[0036] Preferably, when the modified substance used in the modification is a perfluorinated substituted organosilane, the modified inert oxide is prepared by the following steps:

[0037] (A) ultrasonically dispersing an inert oxide into a water-alcohol mixture, adding dropwise an alcohol solution of a perfluoro-substituted organosilane while stirring, and stirring to obtain a silane solution of the inert oxide;

[0038] (B) centrifuging the silane solution of the inert oxide, collecting the solid precipitate, redispersing the solid precipitate, washing it, and drying it to obtain the perfluoro-substituted organosilane-modified inert oxide.

[0039] Preferably, in step (A), the mass volume ratio of the inert oxide to the water-alcohol mixture is 1 g: (100-150) mL.

[0040] Preferably, in step (A), in the water-alcohol mixture, the volume ratio of water to alcohol is 1:(5-50).

[0041] Preferably, in step (A), in the alcohol solution of the perfluoro-substituted organosilane, the volume ratio of the perfluoro-substituted organosilane to the alcohol is 0.03:(10-50).

[0042] Preferably, in step (A), the stirring speed is 400 to 800 rpm, and the stirring time is 1 to 6 hours.

[0043] Preferably, in step (B), the centrifugal rotation speed is 4000-6000 rpm.

[0044] Preferably, when the modified substance used in the modification is an organic amine silane, the modified inert oxide is prepared by the following steps:

[0045] (i) ultrasonically dispersing an inert oxide in dichloromethane, adding dropwise a dichloromethane solution of an organic amine silane while stirring, and stirring to obtain a silane solution of the inert oxide;

[0046] (ii) centrifuging the silane solution of the inert oxide, collecting the solid precipitate, and redispersing the solid precipitate, washing it, and drying it to obtain the inert oxide modified with the organic amine silane.

[0047] Preferably, in step (i), the mass volume ratio of the inert oxide to dichloromethane is 1 g: (100-150) mL.

[0048] Preferably, in step (i), in the dichloromethane solution of the organic amine silane, the volume ratio of the organic amine silane to dichloromethane is 0.03:(10-60).

[0049] Preferably, in step (i), the stirring speed is 400 to 800 rpm, and the stirring time is 1 to 6 hours.

[0050] Preferably, in step (ii), the centrifugal rotation speed is 4000-6000 rpm.

[0051] In a third aspect, the present invention provides a use of the composite noble metal catalyst as described in the first aspect in the preparation of an anode catalyst for PEM water electrolysis, a membrane electrode for PEM water electrolysis, or an electrolytic cell for PEM water electrolysis.

[0052] In a fourth aspect, the present invention provides a membrane electrode for PEM water electrolysis, comprising a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane; wherein the anode catalyst layer comprises the composite precious metal catalyst as described in the first aspect.

[0053] Preferably, the loading of the noble metal element in the anode catalyst layer is 0.100-1.000 mg / cm 2 .

[0054] Preferably, the anode catalyst layer further comprises an ionomer.

[0055] Preferably, the ionomer comprises any one of perfluorosulfonic acid, sulfonated polyetheretherketone resin or sulfonated trifluorostyrene resin or a combination of at least two thereof, preferably perfluorosulfonic acid.

[0056] Preferably, the loading amount of the noble metal element in the cathode catalyst layer is 0.100-1.000 mg / cm 2 .

[0057] Preferably, the proton exchange membrane is a 115 proton exchange membrane.

[0058] In a fifth aspect, the present invention provides a method for preparing a membrane electrode for PEM water electrolysis as described in the fourth aspect, wherein the method for preparing a membrane electrode for PEM water electrolysis comprises the following steps:

[0059] The composite noble metal catalyst, ionomer solution, water and alcohol are mixed, stirred and dispersed, and degassed after ball milling to obtain an anode catalyst layer slurry;

[0060] Applying the anode catalyst layer slurry to one side of the transfer substrate, and after drying, forming the anode catalyst layer;

[0061] Applying the cathode catalyst layer slurry to the other side of the transfer substrate, and after drying, forming the cathode catalyst layer;

[0062] The anode catalyst layer and the cathode catalyst layer are respectively transferred to both sides of the proton exchange membrane by hot pressing transfer to obtain the PEM membrane electrode for water electrolysis.

[0063] Preferably, the composite noble metal catalyst accounts for 15-40% of the total mass of the anode catalyst layer slurry.

[0064] Preferably, the ionomer solution is 5-40% of the mass of the composite noble metal catalyst.

[0065] Preferably, the solid content of the ionomer solution is 15-20 wt%.

[0066] Preferably, the alcohol is a C1-C8 monohydric liquid alcohol and / or a C1-C8 polyhydric liquid alcohol.

[0067] Preferably, the alcohol is selected from any one of ethanol, n-propanol, isopropanol or propylene glycol, or a combination of at least two thereof.

[0068] Preferably, the mass ratio of water to alcohol is (5-8):(2-5).

[0069] Preferably, the ball milling conditions include: 2.0-4.5 mm ZrO 2 Ball milling beads, constant temperature ball milling at 15-25°C, rotation speed of 300-1000rpm, time of 2-12h.

[0070] In a sixth aspect, the present invention provides an electrolytic cell for PEM water electrolysis, wherein the electrolytic cell for PEM water electrolysis comprises the membrane electrode for PEM water electrolysis as described in the fourth aspect.

[0071] Compared with the prior art, the present invention has the following beneficial effects:

[0072] (1) The composite precious metal catalyst of the present invention contains an inert oxide modified with a specific functional group, which significantly improves the slurry stability and increases the viscosity by 750% (@0.5s -1 ), which is more conducive to the coating of large-scale catalytic layer; at the same time, the porosity of the prepared catalytic layer increased by 38%, and there were more mesopores and macropores in the pore size distribution; when applied to actual working conditions, the material transfer process was significantly improved, and under high current density (4A / cm 2 )’s material transfer impedance is reduced by 99%, resulting in a 156mV performance improvement.

[0073] (2) The present invention precisely regulates the pores of the catalyst layer at the molecular level, improves the uniformity and repeatability of the regulation, constructs a pore gradient in multiple dimensions, forms a microporous structure inside the agglomerates, and forms mesopores and macropores outside, further promoting the material transfer process. This not only enhances the electrolysis performance of PEM water electrolysis, but also improves its stability, and ultimately establishes a low-cost, repeatable, and scalable integrated porous anode catalyst layer and its preparation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0075] Figure 1 This is a viscosity curve of the inert oxide provided in Preparation Example 3 before and after modification.

[0076] Figure 2 This is a scanning electron microscope image of the composite precious metal catalyst provided in Example 1 (the scale in the image is 300 nm).

[0077] Figure 3 This is a scanning electron microscope image of the catalyst provided for Comparative Example 3 (the scale bar in the figure is 300 nm).

[0078] Figure 4 This is a comparison chart of the mercury injection test results of the composite precious metal catalyst provided in Example 5 and the catalyst provided in Comparative Example 4.

[0079] Figure 5 The PEM water electrolysis performance curve of the membrane electrode prepared by the composite precious metal catalyst provided in Example 8 and the catalyst provided in Comparative Example 5 is shown.

[0080] Figure 6 The in-situ impedance spectra of the membrane electrode prepared by the composite noble metal catalyst provided in Example 8 and the catalyst provided in Comparative Example 5 are shown. DETAILED DESCRIPTION

[0081] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0082] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0083] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0084] In a first aspect, the present invention provides a composite noble metal catalyst, wherein the composite noble metal catalyst comprises a noble metal oxide catalyst and a modified inert oxide;

[0085] Wherein, the specific surface area of ​​the modified inert oxide is ≥50m 2 / g; and the modification used in the modification includes any one or a combination of at least two of fluorine-containing inorganic substances, perfluorinated substituted organic silanes or organic amine silanes.

[0086] In the present invention, inert oxide nanoparticles modified with surface functional groups with high specific surface area are introduced into the catalyst, and the integrated porous electrode structure is prepared by utilizing the strong interaction with the ionomer when the slurry is prepared, so as to accurately control the porous structure at the molecular level. Nanoparticles with high specific surface area can increase the stability of the slurry and slow down the sedimentation rate of the catalyst particles. At the same time, the modification of the surface functional groups will enhance the interaction with the ionomer, prompting it to form large nanoparticle agglomerates through the strong cross-linking of the ionomer, and forming a large number of microporous structures inside. At the same time, the rapid ionomer adsorption process will form a large number of particle vacuum areas, thereby forming mesoporous and macroporous structures outside the agglomerates, and finally constructing gradient pores, and promoting the working performance expression of PEM water electrolysis through stable and efficient material transmission channels.

[0087] As an optional embodiment, the specific surface area of ​​the modified inert oxide is ≥50m 2 / g, for example, it can be 50m 2 / g, 52m 2 / g, 54m 2 / g, 56m 2 / g, 58m 2 / g, 60m 2 / g, 62m 2 / g, 64m 2 / g, 68m2 / g, 70m 2 / g, 75m 2 / g, 80m 2 / g, 85m 2 / g, 90m 2 / g, 95m 2 / g、100m 2 / g, 120m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 180m 2 / g, 200m 2 / g, etc.

[0088] As an optional embodiment, the fluoride ion-containing inorganic substance includes a fluoride salt.

[0089] As an optional embodiment, the fluoride salt is selected from any one of sodium fluoride, potassium fluoride, lithium fluoride or ammonium fluoride, or a combination of at least two thereof, preferably sodium fluoride.

[0090] As an optional embodiment, the perfluorinated substituted organosilane is selected from any one of trimethoxyfluorosilane, heptadecafluorodecyltrimethoxysilane or 1H, 1H, 2H, 2H perfluorodecyltriethoxysilane or a combination of at least two thereof.

[0091] As an optional embodiment, the organic amine silane is selected from any one of aminopropyltriethoxysilane, aminopropyltrimethoxysilane or anilinomethyltriethoxysilane, or a combination of at least two thereof.

[0092] As an optional embodiment, the inert oxide is selected from any one of titanium oxide, tin oxide, zirconium oxide, niobium oxide, tantalum oxide, tungsten oxide or silicon oxide, or a combination of at least two thereof.

[0093] As an optional embodiment, the mass ratio of the inert oxide to the modifier is 1:(0.03-5.81), for example, it can be 1:0.03, 1:0.05, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:5.5, 1:5.81, etc.

[0094] As an optional embodiment, the noble metal oxide catalyst is selected from any one of ruthenium oxide, rhodium oxide, iridium oxide or platinum oxide, or a combination of at least two thereof, and possible supported noble metal catalysts, preferably iridium oxide.

[0095] As an optional embodiment, the mass ratio of the noble metal oxide catalyst to the modified inert oxide is (1-20):1, for example, it can be 1:1, 2:1, 4:1, 5:1, 6:1, 8:1, 10:1, 12:1, 14:1, 15:1, 16:1, 18:1, 20:1, etc.

[0096] In a second aspect, the present invention provides a method for preparing the composite noble metal catalyst as described in the first aspect, wherein the method for preparing the composite noble metal catalyst comprises the following steps:

[0097] The noble metal oxide catalyst and the modified inert oxide are mixed to obtain the composite noble metal catalyst.

[0098] As an optional embodiment, the mixing method includes any one of stirring, ultrasound, ball milling, solution wet mixing and drying, or a combination of at least two thereof, preferably ball milling.

[0099] As an optional embodiment, the ball milling speed is 200-600rpm, for example, it can be 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, etc., and the ball milling time is 0.5-3h, for example, it can be 0.5h, 0.6h, 0.8h, 1h, 1.2h, 1.4h, 1.5h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.5h, 2.6h, 2.8h, 3h, etc.

[0100] As an optional embodiment, when the modified substance used in the modification is a fluorine-containing inorganic substance, the modified inert oxide is prepared by the following steps:

[0101] (a) ultrasonically dispersing an inert oxide into a solution of a fluoride ion inorganic substance, adjusting the pH of the system to 2.5 to 3.5, and stirring to obtain a fluoride ion solution of the inert oxide;

[0102] (b) centrifuging the fluoride ion solution of the inert oxide, collecting the solid precipitate, and then redispersing the solid precipitate, washing it, and drying it to obtain the fluoride ion modified inert oxide.

[0103] As an optional embodiment, in step (a), the mass volume ratio of the solution of the inert oxide and the fluorine-containing inorganic substance is 1g:(100-150)mL, for example, it can be 1g:100mL, 1g:105mL, 1g:110mL, 1g:115mL, 1g:120mL, 1g:125mL, 1g:130mL, 1g:135mL, 1g:140mL, 1g:145mL, 1g:150mL, etc.

[0104] As an optional embodiment, in step (a), the concentration of the solution containing fluorine ions and inorganic substances is 0.1-2M, for example, it can be 0.1M, 0.2M, 0.4M, 0.6M, 0.8M, 1M, 1.2M, 1.4M, 1.6M, 1.8M, 2M, etc., preferably 1M.

[0105] As an optional embodiment, in step (a), the solvent in the solution of the fluorine ion inorganic substance is selected from any one of water, ethanol or methanol or a combination of at least two thereof, preferably water.

[0106] As an optional embodiment, in step (a), the reagent used to adjust the pH of the system is an inorganic acid, preferably any one of nitric acid, sulfuric acid, hydrochloric acid or phosphoric acid, or a combination of at least two thereof, more preferably nitric acid.

[0107] As an optional embodiment, in step (a), the concentration of the inorganic acid is 0.1-1M, for example, 0.1M, 0.2M, 0.4M, 0.5M, 0.6M, 0.8M, 1M, preferably 0.5M.

[0108] As an optional embodiment, in step (a), the stirring speed is 400-800 rpm, for example, it can be 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, etc., and the stirring time is 1-3 h, for example, it can be 1 h, 1.2 h, 1.4 h, 1.5 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.5 h, 2.6 h, 2.8 h, 3 h, etc.

[0109] As an optional embodiment, in step (b), the centrifugal rotation speed is 4000-6000rpm, for example, it can be 4000rpm, 4200rpm, 4400rpm, 4500rpm, 4600rpm, 4800rpm, 5000rpm, 5200rpm, 5400rpm, 5500rpm, 5600rpm, 5800rpm, 6000rpm, etc., preferably 5000rpm.

[0110] As an optional embodiment, in step (b), during the redispersion process, the solvent used is selected from any one of water, ethanol or methanol, or a combination of at least two of them, preferably water.

[0111] As an optional embodiment, in step (b), during the washing process, the washing liquid used is an inorganic acid, preferably any one of nitric acid, sulfuric acid, hydrochloric acid or phosphoric acid, or a combination of at least two thereof, more preferably nitric acid.

[0112] As an optional embodiment, in step (b), the concentration of the inorganic acid is 0.1-1M, for example, 0.1M, 0.2M, 0.4M, 0.5M, 0.6M, 0.8M, 1M, preferably 0.5M.

[0113] It should be noted that during washing, the system needs to maintain the pH value adjusted above.

[0114] As an optional embodiment, when the modified substance used in the modification is a perfluoro-substituted organosilane, the modified inert oxide is prepared by the following steps:

[0115] (A) ultrasonically dispersing an inert oxide into a water-alcohol mixture, adding dropwise an alcohol solution of a perfluoro-substituted organosilane while stirring, and stirring to obtain a silane solution of the inert oxide;

[0116] (B) centrifuging the silane solution of the inert oxide, collecting the solid precipitate, redispersing the solid precipitate, washing it, and drying it to obtain the perfluoro-substituted organosilane-modified inert oxide.

[0117] As an optional embodiment, in step (A), the mass volume ratio of the inert oxide and the water-alcohol mixture is 1g:(100-150)mL.

[0118] As an optional embodiment, in step (A), in the water-alcohol mixture, the volume ratio of water to alcohol is 1:(5-50), for example, it can be 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, etc.

[0119] As an optional embodiment, in step (A), in the alcohol solution of the perfluoro-substituted organosilane, the volume ratio of the perfluoro-substituted organosilane to the alcohol is 0.03:(10-50), for example, it can be 0.03:10, 0.03:15, 0.03:20, 0.03:25, 0.0330, 0.03:35, 0.03:40, 0.03:45, 0.03:50, etc.

[0120] As an optional embodiment, in step (A), the stirring speed is 400-800 rpm, for example, it can be 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, etc., and the stirring time is 1-6 h, for example, it can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, etc.

[0121] As an optional embodiment, in step (B), the centrifugal rotation speed is 4000-6000rpm, for example, it can be 4000rpm, 4200rpm, 4400rpm, 4500rpm, 4600rpm, 4800rpm, 5000rpm, 5200rpm, 5400rpm, 5500rpm, 5600rpm, 5800rpm, 6000rpm, etc., preferably 5000rpm.

[0122] As an optional embodiment, in step (B), during the redispersion process, the solvent used is selected from any one of water, ethanol or methanol, or a combination of at least two of them, preferably water.

[0123] As an optional embodiment, in step (B), during the washing process, the solvent used is selected from water, preferably ultrapure water.

[0124] As an optional embodiment, when the modified substance used in the modification is an organic amine silane, the modified inert oxide is prepared by the following steps:

[0125] (i) ultrasonically dispersing an inert oxide in dichloromethane, adding dropwise a dichloromethane solution of an organic amine silane while stirring, and stirring to obtain a silane solution of the inert oxide;

[0126] (ii) centrifuging the silane solution of the inert oxide, collecting the solid precipitate, and redispersing the solid precipitate, washing it, and drying it to obtain the inert oxide modified with the organic amine silane.

[0127] As an optional embodiment, in step (i), the mass volume ratio of the inert oxide and dichloromethane is 1g:(100-150)mL, for example, it can be 1g:100mL, 1g:105mL, 1g:110mL, 1g:115mL, 1g:120mL, 1g:125mL, 1g:130mL, 1g:135mL, 1g:140mL, 1g:145mL, 1g:150mL, etc.

[0128] As an optional embodiment, in step (i), in the dichloromethane solution of the organic amine silane, the volume ratio of the organic amine silane to dichloromethane is 0.03:(10-60), for example, it can be 0.03:10, 0.03:15, 0.03:20, 0.03:25, 0.0330, 0.03:35, 0.03:40, 0.03:45, 0.03:50, 0.03:55, 0.03:60, etc.

[0129] As an optional embodiment, in step (i), the stirring speed is 400-800 rpm, for example, it can be 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, etc., and the stirring time is 1-6 h, for example, it can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, etc.

[0130] As an optional embodiment, in step (ii), the centrifugal rotation speed is 4000-6000 rpm, for example, it can be 4000 rpm, 4200 rpm, 4400 rpm, 4500 rpm, 4600 rpm, 4800 rpm, 5000 rpm, 5200 rpm, 5400 rpm, 5500 rpm, 5600 rpm, 5800 rpm, 6000 rpm, etc., preferably 5000 rpm.

[0131] As an optional embodiment, in step (ii), during the redispersion process, the solvent used is selected from any one of water, ethanol or methanol, or a combination of at least two of them, preferably water.

[0132] As an optional embodiment, in step (ii), during the washing process, the solvent used is selected from water, preferably ultrapure water.

[0133] In a third aspect, the present invention provides a use of the composite noble metal catalyst as described in the first aspect in the preparation of an anode catalyst for PEM water electrolysis, a membrane electrode for PEM water electrolysis, or an electrolytic cell for PEM water electrolysis.

[0134] In a fourth aspect, the present invention provides a membrane electrode for PEM water electrolysis, comprising a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane; wherein the anode catalyst layer comprises the composite precious metal catalyst as described in the first aspect.

[0135] As an optional embodiment, the loading amount of the noble metal element in the anode catalyst layer is 0.100 to 1.000 mg / cm 2, for example, it can be 0.100 mg / cm 2 , 0.200mg / cm 2 , 0.300mg / cm 2 , 0.400mg / cm 2 , 0.500mg / cm 2 , 0.600mg / cm 2 , 0.700mg / cm 2 , 0.800mg / cm 2 , 0.900mg / cm 2 , 1.000mg / cm 2 wait.

[0136] As an optional embodiment, the anode catalyst layer further includes an ionomer.

[0137] As an optional embodiment, the ionomer includes any one of perfluorosulfonic acid, sulfonated polyetheretherketone resin or sulfonated trifluorostyrene resin, or a combination of at least two thereof, preferably perfluorosulfonic acid.

[0138] As an optional embodiment, the loading amount of the noble metal element in the cathode catalyst layer is 0.100 to 1.000 mg / cm 2 , for example, it can be 0.100 mg / cm 2 , 0.200mg / cm 2 , 0.300mg / cm 2 , 0.400mg / cm 2 , 0.500mg / cm 2 , 0.600mg / cm 2 , 0.700mg / cm 2 , 0.800mg / cm 2 , 0.900mg / cm 2 , 1.000mg / cm 2 wait.

[0139] As an optional embodiment, the proton exchange membrane is a 115 proton exchange membrane.

[0140] In a fifth aspect, the present invention provides a method for preparing a membrane electrode for PEM water electrolysis as described in the fourth aspect, wherein the method for preparing a membrane electrode for PEM water electrolysis comprises the following steps:

[0141] The composite noble metal catalyst, ionomer solution, water and alcohol are mixed, stirred and dispersed, and degassed after ball milling to obtain an anode catalyst layer slurry;

[0142] Applying the anode catalyst layer slurry to one side of the transfer substrate, and after drying, forming the anode catalyst layer;

[0143] Applying the cathode catalyst layer slurry to the other side of the transfer substrate, and after drying, forming the cathode catalyst layer;

[0144] The anode catalyst layer and the cathode catalyst layer are respectively transferred to both sides of the proton exchange membrane by hot pressing transfer to obtain the PEM membrane electrode for water electrolysis.

[0145] As an optional embodiment, the composite precious metal catalyst accounts for 15-40% of the total mass of the anode catalyst layer slurry, for example, it can be 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40% and the like.

[0146] As an optional embodiment, the ionomer solution is 5-40% of the mass of the composite precious metal catalyst, for example, it can be 5%, 6%, 8%, 10%, 12%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, etc.

[0147] As an optional implementation, the solid content of the ionomer solution is 15-20wt%, for example, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% and the like.

[0148] As an optional embodiment, the alcohol is a C1-C8 monohydric liquid alcohol and / or a C1-C8 polyhydric liquid alcohol.

[0149] As an optional embodiment, the alcohol is selected from any one of ethanol, n-propanol, isopropanol or propylene glycol, or a combination of at least two thereof.

[0150] As an optional embodiment, the mass ratio of water to alcohol is (5-8):(2-5);

[0151] Here, “5-8” may be, for example, 5, 5.5, 6, 6.5, 7, 7.5, 8, etc.;

[0152] Here, “2-5” can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.

[0153] As an optional embodiment, the ball milling conditions include: 2.0-4.5 mm ZrO 2 Ball milling beads, constant temperature ball milling at 15-25°C, rotation speed of 300-1000rpm, time of 2-12h.

[0154] As an optional embodiment, the ball milling conditions include: 2.0-4.5 mm ZrO 2 Ball milling beads, constant temperature ball milling at 15-25°C, rotation speed of 300-1000rpm, time of 2-12h.

[0155] As an optional embodiment, the ZrO 2 The particle size of the ball mill beads is 2.0 to 4.5 mm, for example, 2.0 mm, 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3 mm, 3.2 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.8 mm, 4 mm, 4.2 mm, 4.4 mm, 4.5 mm, etc.

[0156] As an optional embodiment, the ball milling temperature is 15-25°C, for example, it can be 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, etc.

[0157] As an optional embodiment, the rotation speed of the ball mill is 300-1000rpm, for example, it can be 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, etc.

[0158] As an optional embodiment, the ball milling time is 2 to 12 hours, for example, it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, etc.

[0159] In a sixth aspect, the present invention provides an electrolytic cell for PEM water electrolysis, wherein the electrolytic cell for PEM water electrolysis comprises the membrane electrode for PEM water electrolysis described in the fourth aspect.

[0160] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0161] Preparation Example 1

[0162] This preparation example provides a modified inert oxide, and the modified inert oxide is prepared by the following steps:

[0163] 1g TiO 2 (Specific surface area is 60m 2 / g) was ultrasonically dispersed into 125 mL of 1M NaF aqueous solution, and 0.5M HNO was added dropwise at 600 rpm while stirring. 3 The solution was adjusted to pH 3 and stirred at 400 rpm for 2 h to form a uniformly dispersed solution. The solid precipitate was re-dispersed in 0.5 M HNO 3 solution and treated with 0.5 M HNO 3 The sample was washed three times to remove the unexchanged F ions, and finally vacuum dried overnight to obtain fluoride ion-modified TiO 2 .

[0164] Preparation Example 2

[0165] This preparation example provides a modified inert oxide, which differs from Preparation Example 1 only in that sodium fluoride is replaced by an equal amount of potassium fluoride, and the other steps are exactly the same as Preparation Example 1.

[0166] Preparation Example 3

[0167] This preparation example provides a modified inert oxide, and the modified inert oxide is prepared by the following steps:

[0168] 0.03 mL of heptadecafluorodecyltrimethoxysilane was dissolved in 30 mL of ethanol and ultrasonically dispersed for 2 h to form solution A. 1 g of Nb 2 O 5 (Specific surface area is 30m 2 / g) ultrasonically dispersed into 100 mL of water-alcohol mixture (V 水 :V 乙醇 =1:25); adding the solution A dropwise while stirring at a speed of 500 rpm, and then stirring at a speed of 300 rpm for 4 hours to form a uniformly dispersed solution; centrifuging at a speed of 5000 rpm, re-dispersing the solid precipitate after centrifugation in the solvent, and washing it with ultrapure water for 3 times to remove the unabsorbed molecules, and finally vacuum drying the sample overnight to obtain organofluorosilane-modified Nb 2 O 5 .

[0169] Preparation Example 4

[0170] This preparation example provides a modified inert oxide, which differs from Preparation Example 3 only in that heptadecafluorodecyltrimethoxysilane is replaced with an equal amount of 1H,1H,2H,2Hperfluorodecyltriethoxysilane, and the other steps are exactly the same as Preparation Example 3.

[0171] Preparation Example 5

[0172] This preparation example provides a modified inert oxide, and the modified inert oxide is prepared by the following steps:

[0173] 0.03 mL of phenylaminomethyltriethoxysilane was dissolved in 40 mL of dichloromethane and ultrasonically dispersed for 2 h to form solution A. 1 g of SnO 2 (Specific surface area is 80m 2 / g) was ultrasonically dispersed in 60mL of dichloromethane; the solution A was added dropwise at a speed of 800rpm while stirring, and then stirred at a speed of 600rpm for 5h to form a uniformly dispersed solution; centrifuged at a speed of 5000rpm, the solid precipitate after centrifugation was re-dispersed in an aqueous solvent, and washed with ultrapure water for 3 times to remove the unabsorbed molecules, and finally the sample was vacuum dried overnight to obtain organofluorosilane-modified SnO 2 .

[0174] Preparation Example 6

[0175] This preparation example provides a modified inert oxide, which differs from Preparation Example 5 only in that anilinomethyltriethoxysilane is replaced with an equal amount of aminopropyltrimethoxysilane, and the other steps are exactly the same as Preparation Example 5.

[0176] Example 1

[0177] This embodiment provides a composite noble metal catalyst, which is prepared by the following steps:

[0178] The iridium oxide particles were mixed with the modified inert oxide provided in Preparation Example 1 at a mass ratio of 10:1, and ball-milled for 2 hours at a ball-milling speed of 400 rpm to obtain a composite noble metal catalyst.

[0179] Example 2

[0180] This embodiment provides a composite noble metal catalyst, which is prepared by the following steps:

[0181] The iridium oxide particles were mixed with the modified inert oxide provided in Preparation Example 1 at a mass ratio of 15:1, and ball-milled for 0.5 h at a ball-milling speed of 600 rpm to obtain a composite noble metal catalyst.

[0182] Example 3

[0183] This embodiment provides a composite noble metal catalyst, which is prepared by the following steps:

[0184] The iridium oxide particles were mixed with the modified inert oxide provided in Preparation Example 1 at a mass ratio of 5:1, and ball-milled for 3 hours at a ball-milling speed of 200 rpm to obtain a composite noble metal catalyst.

[0185] Example 4

[0186] This embodiment provides a composite precious metal catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by the modified inert oxide provided in Preparation Example 2, and the other steps are consistent with Example 1.

[0187] Example 5

[0188] This embodiment provides a composite precious metal catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by the modified inert oxide provided in Preparation Example 3, and the other steps are consistent with Example 1.

[0189] Example 6

[0190] This embodiment provides a composite precious metal catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by the modified inert oxide provided in Preparation Example 4, and the other steps are consistent with Example 1.

[0191] Example 7

[0192] This embodiment provides a composite precious metal catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by the modified inert oxide provided in Preparation Example 5, and the other steps are consistent with Example 1.

[0193] Example 8

[0194] This embodiment provides a composite precious metal catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by the modified inert oxide provided in Preparation Example 6, and the other steps are consistent with Example 1.

[0195] Example 9

[0196] This embodiment provides a composite precious metal catalyst, which is different from Embodiment 1 only in that the iridium oxide particles are replaced with an equal amount of ruthenium oxide particles, and the other steps are consistent with Embodiment 1.

[0197] Example 10

[0198] This embodiment provides a composite precious metal catalyst, which is different from Example 1 only in that the mass ratio of iridium oxide particles to the modified inert oxide provided in Preparation Example 1 is 25:1, and the other steps are consistent with Example 1.

[0199] Embodiment 11

[0200] This embodiment provides a composite precious metal catalyst, which is different from Example 1 only in that the mass ratio of iridium oxide particles to the modified inert oxide provided in Preparation Example 1 is 0.5:1, and the other steps are consistent with Example 1.

[0201] Comparative Example 1

[0202] This comparative example provides a catalyst, which is iridium oxide.

[0203] Comparative Example 2

[0204] This comparative example provides a catalyst, which is ruthenium oxide.

[0205] Comparative Example 3

[0206] This comparative example provides a catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by unmodified TiO 2 , the other steps are exactly the same as those in Example 1.

[0207] Comparative Example 4

[0208] This comparative example provides a catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by unmodified Nb 2 O 5 , the other steps are exactly the same as those in Example 1.

[0209] Comparative Example 5

[0210] This comparative example provides a catalyst, which is different from Example 1 only in that the modified inert oxide provided in Preparation Example 1 is replaced by unmodified SnO 2 , the other steps are exactly the same as those in Example 1.

[0211] Test Example 1

[0212] Viscosity test

[0213] Test samples: the composite noble metal catalyst provided in Example 1, and the composite noble metal catalysts provided in Examples 4 to 8.

[0214] Test method:

[0215] (1) Deionized water, PEM water electrolysis anode catalyst, ionomer solution and alcohol are added to a glass bottle in sequence, the glass bottle is placed on a magnetic stirrer, and after stirring and dispersing, the solution is transferred to a ball milling jar containing ball milling beads and ball milled under constant temperature;

[0216] The anode catalyst is a composite precious metal catalyst, and the mass of the catalyst accounts for 25wt% of the total mass of the slurry; the ionomer solution is a perfluorosulfonic acid solution, and the mass of the ionomer solution is 20wt% of the mass of the catalyst; the alcohol is isopropanol, and the mass ratio of the added deionized water to the total liquid alcohol is 6:4;

[0217] Among them, the ball milling conditions are: 3.5mm ZrO 2 The beads were ball milled at a constant temperature of 20°C, a rotation speed of 650 rpm, and a time of 7 h.

[0218] (2) After ball milling and dispersion, the slurry is mixed and degassed using a degassing machine to obtain an anode catalyst layer slurry.

[0219] (3) The viscosity of the above sample slurries was tested at different shear rates.

[0220] The test results are shown in Table 1 and Figure 1 As shown:

[0221] Table 1

[0222]

[0223] As shown in Table 1, at a shear rate of 1s -1 Under the conditions of shear rate of 10s -1 Under the conditions of shear rate of 100s -1 Under the condition, the viscosity of the modified inert oxide provided by the present invention is increased to 0.039-0.058 Pa·s, which shows that the viscosity of the inert oxide is significantly increased after being surface-modified by any one or a combination of at least two of fluorine-containing inorganic substances, perfluorinated organic silanes or organic amine silanes.

[0224] Test Example 2

[0225] Pore ​​size and porosity testing

[0226] Test samples: the composite noble metal catalysts provided in Examples 1 to 11 and the catalysts provided in Comparative Examples 1 to 5.

[0227] Test method: The pore size of each catalyst sample was tested by scanning electron microscopy, and the porosity of each catalyst sample was tested by mercury injection.

[0228] The test results are shown in Table 2 and Figure 2 , Figure 3 and Figure 4 As shown:

[0229] Table 2

[0230]

[0231]

[0232] As shown in Table 2, the pore size of the composite noble metal catalyst of the present invention is 520-675 nm, and the porosity of the composite noble metal catalyst of the present invention is 40.26-53.13%. This shows that the composite noble metal catalyst of the present invention has more pores, a larger pore size, and an obvious macroporous structure, which is conducive to building a stable material transmission channel; at the same time, the composite noble metal catalyst has a higher porosity, further improving the ability of material transmission.

[0233] Application Example 1

[0234] This application example provides a PEM membrane electrode for water electrolysis, and the PEM membrane electrode for water electrolysis is prepared by the following steps:

[0235] (1) Deionized water, PEM water electrolysis anode catalyst, ionomer solution and alcohol are added to a glass bottle in sequence, the glass bottle is placed on a magnetic stirrer, and after stirring and dispersing, the solution is transferred to a ball milling jar containing ball milling beads and ball milled under constant temperature;

[0236] The anode catalyst is the composite noble metal catalyst provided in Example 1, and the mass of the catalyst accounts for 25wt% of the total mass of the slurry; the ionomer solution is a perfluorosulfonic acid solution, and the mass of the ionomer solution is 20wt% of the mass of the catalyst; the alcohol is isopropanol, and the mass ratio of the added deionized water to the total liquid alcohol is 6:4;

[0237] Among them, the ball milling conditions are: 3.5mm ZrO 2 The beads were ball milled at a constant temperature of 20°C, a rotation speed of 650 rpm, and a time of 7 h.

[0238] (2) After ball milling and dispersion, the slurry is mixed and degassed using a degassing machine to obtain an anode catalyst layer slurry.

[0239] (3) Coating on PTFE membrane using a slot coater (loading 0.5 mg Ir / cm 2 ).

[0240] (4) After drying, XRF is used to detect whether the average iridium loading in the catalyst coating meets the standard.

[0241] (5) Then the coating was applied on the PTFE membrane with a loading of 0.3 mg Pt / cm 2 The cathode catalyst layer and 115 proton exchange membrane were prepared into catalyst coated membrane (CCM) by hot pressing transfer.

[0242] Application Example 2

[0243] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 2 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0244] Application Example 3

[0245] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 3 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0246] Application Example 4

[0247] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 4 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0248] Application Example 5

[0249] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 5 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0250] Application Example 6

[0251] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 6 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0252] Application Example 7

[0253] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 7 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0254] Application Example 8

[0255] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 8 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0256] Application Example 9

[0257] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 9 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0258] Application Example 10

[0259] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 10 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0260] Application Example 11

[0261] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a composite precious metal catalyst provided in Example 11 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0262] Comparative application example 1

[0263] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 1 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0264] Comparative Application Example 2

[0265] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 2 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0266] Comparative Application Example 3

[0267] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 3 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0268] Comparative Application Example 4

[0269] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 4 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0270] Comparative Application Example 5

[0271] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the composite precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 5 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0272] Test Example 3

[0273] Multi-channel device performance testing

[0274] Test samples: PEM membrane electrodes for water electrolysis provided in Application Examples 1 to 11, and PEM membrane electrodes for water electrolysis provided in Comparative Application Examples 1 to 5.

[0275] Test method:

[0276] (1) Assembly of the electrolytic cell: The electrolytic cell was assembled in the order of insulating end plate, cathode plate, 0.15 mm gasket, carbon paper, membrane electrode (CCM), 2.05 mm gasket, titanium felt, titanium mesh and anode plate. The electrolytic cell was tightened diagonally with a torque wrench (3 N·m) and the electrode clamp was clamped. Water was passed under the working condition of 80°C and the electrochemical performance test was carried out, including polarization performance test and 2A / cm 2 Stability test under current density.

[0277] (2) Polarization performance test method: During the PEMWE working condition test, the program is set to record the current density from the low current density of 0.025A / cm 2 The cell pressure of the electrolytic cell is plotted as a function of the current density at a high current density of 6 A / cm2.

[0278] (3) Stability test method: Under the PEMWE working condition, the electrochemical stability test was carried out by chronopotentiometry. 2 The stability test was carried out for 180 hours. During the stability test, the real-time current and voltage values ​​were recorded.

[0279] The test results are shown in Tables 3 and 4 below. Figure 5-6 As shown:

[0280] Table 3

[0281]

[0282] Table 4

[0283]

[0284]

[0285] From Table 3 to Table 4 above and Figure 5-6As shown, the PEM water electrolysis performance of each sample prepared using the composite noble metal catalyst of the present invention as the anode catalyst is significantly better than that of the control sample; and the material transfer impedance of the experimental sample at low frequency is significantly smaller than that of the control sample, and has faster electrochemical oxygen evolution reaction kinetics.

[0286] In summary, the high specific surface area of ​​the inert oxide described in the present invention can promote the stability of the slurry and prevent particle sedimentation during the pore formation process; the functional groups modified on the surface of the compound: inorganic F ions, organic F molecules and organic amine molecules, can react with the sulfonic acid side chains of the ionomer through strong chemical bonds to achieve the effect of rapid adsorption, thereby constructing aggregates and realizing gradient pores; the spontaneous formation of pores is precisely controlled at the molecular level, thereby constructing an integrated porous catalytic layer.

[0287] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite noble metal catalyst, characterized in that: The composite noble metal catalyst comprises a noble metal oxide catalyst and a modified inert oxide; Wherein, the specific surface area of ​​the modified inert oxide is ≥50m 2 / g; and the modification used in the modification includes any one or a combination of at least two of fluorine-containing inorganic substances, perfluorinated substituted organic silanes or organic amine silanes.

2. The composite noble metal catalyst according to claim 1, characterized in that The fluoride ion-containing inorganic substance includes a fluoride salt; Preferably, the fluoride salt is selected from any one of sodium fluoride, potassium fluoride, lithium fluoride or ammonium fluoride or a combination of at least two thereof, preferably sodium fluoride; Preferably, the perfluorinated organosilane is selected from any one or a combination of at least two of trimethoxyfluorosilane, heptadecafluorodecyltrimethoxysilane or 1H, 1H, 2H, 2H perfluorodecyltriethoxysilane; Preferably, the organic amine silane is selected from any one or a combination of at least two of aminopropyltriethoxysilane, aminopropyltrimethoxysilane or anilinomethyltriethoxysilane; Preferably, the inert oxide is selected from any one or a combination of at least two of titanium oxide, tin oxide, zirconium oxide, niobium oxide, tantalum oxide, tungsten oxide or silicon oxide; Preferably, the mass ratio of the inert oxide to the modifier is 1:(0.03-5.81); Preferably, the noble metal oxide catalyst is selected from any one or a combination of at least two of ruthenium oxide, rhodium oxide, iridium oxide or platinum oxide; Preferably, the mass ratio of the noble metal oxide catalyst to the modified inert oxide is (1-20):

1.

3. A method for preparing a composite noble metal catalyst according to claim 1 or 2, characterized in that: The preparation method comprises: The noble metal oxide catalyst and the modified inert oxide are mixed to obtain the composite noble metal catalyst.

4. The method for preparing a composite noble metal catalyst according to claim 3, characterized in that: The mixing method includes any one of stirring, ultrasound, ball milling, solution wet mixing and drying, or a combination of at least two thereof, preferably ball milling; Preferably, the ball milling speed is 200 to 600 rpm, and the ball milling time is 0.5 to 3 h; Preferably, when the modified substance used in the modification is a fluorine-containing inorganic substance, the modified inert oxide is prepared by the following steps: (a) ultrasonically dispersing an inert oxide into a solution of a fluoride ion inorganic substance, adjusting the pH of the system to 2.5 to 3.5, and stirring to obtain a fluoride ion solution of the inert oxide; (b) centrifuging the fluoride ion solution of the inert oxide, collecting the solid precipitate, and then redispersing the solid precipitate, washing it, and drying it to obtain the fluoride ion-modified inert oxide; Preferably, in step (a), the mass volume ratio of the inert oxide and the solution of the fluorine ion-containing inorganic substance is 1 g: (100-150) mL; Preferably, in step (a), the concentration of the solution containing the fluorine ion inorganic substance is 0.1 to 10 M; Preferably, in step (a), the solvent in the solution of the fluorine ion inorganic substance is selected from any one or a combination of at least two of water, ethanol or methanol, preferably water; Preferably, in step (a), the reagent used to adjust the pH of the system is an inorganic acid, preferably any one or a combination of at least two of nitric acid, sulfuric acid, hydrochloric acid or phosphoric acid, more preferably nitric acid; Preferably, in step (a), the concentration of the inorganic acid is 0.1 to 1 M; Preferably, in step (a), the stirring speed is 400 to 800 rpm, and the stirring time is 1 to 3 hours; Preferably, in step (b), the centrifugal speed is 4000-6000 rpm; Preferably, when the modified substance used in the modification is a perfluorinated substituted organosilane, the modified inert oxide is prepared by the following steps: (A) ultrasonically dispersing an inert oxide into a water-alcohol mixture, adding dropwise an alcohol solution of a perfluoro-substituted organosilane while stirring, and stirring to obtain a silane solution of the inert oxide; (B) centrifuging the silane solution of the inert oxide, collecting the solid precipitate, redispersing the solid precipitate, washing it, and drying it to obtain the perfluoro-substituted organosilane-modified inert oxide; Preferably, in step (A), the mass volume ratio of the inert oxide and the water-alcohol mixture is 1 g: (100-150) mL; Preferably, in step (A), in the water-alcohol mixture, the volume ratio of water to alcohol is 1:(5-50); Preferably, in step (A), in the alcohol solution of the perfluoro-substituted organosilane, the volume ratio of the perfluoro-substituted organosilane to the alcohol is 0.03:(10-50); Preferably, in step (A), the stirring speed is 400 to 800 rpm, and the stirring time is 1 to 6 hours; Preferably, in step (B), the centrifugal speed is 4000-6000 rpm; Preferably, when the modified substance used in the modification is an organic amine silane, the modified inert oxide is prepared by the following steps: (i) ultrasonically dispersing an inert oxide in dichloromethane, adding dropwise a dichloromethane solution of an organic amine silane while stirring, and stirring to obtain a silane solution of the inert oxide; (ii) centrifuging the silane solution of the inert oxide, collecting the solid precipitate, and then redispersing the solid precipitate, washing it, and drying it to obtain an inert oxide modified with an organic amine silane; Preferably, in step (i), the mass volume ratio of the inert oxide to dichloromethane is 1 g: (100-150) mL; Preferably, in step (i), in the dichloromethane solution of the organic amine silane, the volume ratio of the organic amine silane to dichloromethane is 0.03:(10-60); Preferably, in step (i), the stirring speed is 400 to 800 rpm, and the stirring time is 1 to 6 hours; Preferably, in step (ii), the centrifugal rotation speed is 4000-6000 rpm.

5. Use of the composite noble metal catalyst according to claim 1 or 2 in the preparation of an anode catalyst for PEM water electrolysis, a membrane electrode for PEM water electrolysis or an electrolytic cell for PEM water electrolysis.

6. A membrane electrode for PEM water electrolysis, characterized in that: The membrane electrode for PEM water electrolysis comprises a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane; wherein the anode catalyst layer comprises the composite precious metal catalyst according to claim 1 or 2.

7. The membrane electrode for PEM water electrolysis according to claim 6, characterized in that: The loading of the noble metal element in the anode catalyst layer is 0.100-1.000 mg / cm 2 ; Preferably, the anode catalyst layer further comprises an ionomer; Preferably, the ionomer comprises any one or a combination of at least two of perfluorosulfonic acid, sulfonated polyetheretherketone resin or sulfonated trifluorostyrene resin, preferably perfluorosulfonic acid; Preferably, the loading of the noble metal element in the cathode catalyst layer is 0.100-1.000 mg / cm 2 ; Preferably, the proton exchange membrane is a 115 proton exchange membrane.

8. A method for preparing a membrane electrode for PEM water electrolysis according to claim 6 or 7, characterized in that: The preparation method of the PEM membrane electrode for water electrolysis comprises the following steps: The composite noble metal catalyst, ionomer solution, water and alcohol are mixed, stirred and dispersed, and degassed after ball milling to obtain an anode catalyst layer slurry; Applying the anode catalyst layer slurry to one side of the transfer substrate, and after drying, forming the anode catalyst layer; Applying the cathode catalyst layer slurry to the other side of the transfer substrate, and after drying, forming the cathode catalyst layer; The anode catalyst layer and the cathode catalyst layer are respectively transferred to both sides of the proton exchange membrane by hot pressing transfer to obtain the PEM membrane electrode for water electrolysis.

9. The method for preparing a membrane electrode for PEM water electrolysis according to claim 8, characterized in that: The composite noble metal catalyst accounts for 15-40% of the total mass of the anode catalyst layer slurry; Preferably, the ionomer solution is 5 to 40% of the mass of the composite noble metal catalyst; Preferably, the solid content of the ionomer solution is 15-20 wt%; Preferably, the alcohol is a C1-C8 monohydric liquid alcohol and / or a C1-C8 polyhydric liquid alcohol; Preferably, the alcohol is selected from any one or a combination of at least two of ethanol, n-propanol, isopropanol or propylene glycol; Preferably, the mass ratio of water to alcohol is (5-8):(2-5); Preferably, the ball milling conditions include: ZrO2 ball milling beads of 2.0 to 4.5 mm, constant temperature ball milling at 15 to 25 degrees Celsius, a rotation speed of 300 to 1000 rpm, and a time of 2 to 12 hours.

10. A PEM electrolytic cell for water electrolysis, characterized in that: The PEM water electrolysis electrolysis cell comprises the PEM water electrolysis membrane electrode according to claim 6 or 7.

Citation Information

Patent Citations

  • High-performance solid oxide electrolytic tank support

    CN103319182A

  • Direct-methanol fuel cell nano-porous structural film electrode construction method based on sacrificial template method

    CN103531826A

  • Method for preparing porous membrane electrode by using ice template method

    CN110212224A

  • Fuel cell membrane electrode and preparation method thereof

    CN113839052A

  • Fuel cell catalyst layer and preparation method and application thereof

    CN118213541A

Cited By

  • Chemical copper plating nano modifier for SLP type support plate aMSAP process and preparation method thereof

    CN120366754A

  • Preparation method and application of phosphorus-doped silicon oxide material

    CN121288850A

  • A method for preparing and using a phosphorus-doped silicon oxide material

    CN121288850B